The Grotesque Body and Ageing in A.S.Byatt’s Short Fiction (American & British Studies Annual, 2016)
The paper deals with the work of the novelist Antonia Susan Byatt who became attracted to the short story genre which she often uses to express her fantastic ideas concerning the human body and its transformations, including ageing and death. Byatt often presents the human body as grotesque – it is deformed, hybrid, and/or monstrous. In her stories, the human bodies changed by circumstances or other factors usually signify the characters’ crisis in which they create new autonomies, new forms of existence. The paper discusses Byatt’s way of using the grotesque in depicting ageing and illness of her protagonists. The analysis is focused on two short stories from Little Black Book of Stories (2003) and explores the protagonists’ identity disintegration and body transformation as a result of inevitable life processes and the perception of human life as fragile and unstable.
Keywords: ageing; A.S.Byatt; body; grotesque; body transformation; identity disintegration